The Geographical Distribution of Cutaneous Leishmaniasis Causative Agents in Iran and Its Neighboring Countries, A Review - Ghatee, Mohammad Amin; Taylor, Walter R.; Karamian, Mehdi (Frontiers in Public Health, 2020)
Leishmania tropica and L. major are the main cause of anthroponotic (ACL) and zoonotic cutaneous leishmaniasis (ZCL), respectively in the Old World. L. infantum and L. donovani which are important causes of visceral leishmaniasis, have also been reported occasionally in CL patients. The present study investigates the current distribution of causative species of CL in Iran and neighbouring countries in the Middle East. There has been expansion of L. tropica into new urban and rural foci in Iran, with well documented cases of visceralization, a substantial increase of CL in Syria and the emergence of new foci and outbreaks in Turkey and Iraq, especially due to L. major. Civil war in Syria and Iraq, population movement, poverty and climatic change play important roles in the changing CL distribution in this region. Control programs should adopt a multidisciplinary approach based on active surveillance and case finding, especially in vulnerable refugees populations, determination of hazard maps for CL hot points using GIS and other advanced technology, the free distribution of drugs, rodent control, and greater community engagement in poor and marginalised populations. Comprehensive molecular studies that could show the species and strains of Leishmania in different areas of each country can give better view from distribution of CL in this region.